A new world beyond boundaries: an exploration of virtual reality within drama therapeutic sessions by assessing role theory & method in correlation to avatars for clients displaying anxiety symptoms. - Mokgatle, Lebogang (My University, 2023)
This paper explored virtual reality as a means of providing a Drama Therapy session, particularly using Role Method and Theory in correlation with the use of avatars. The research was intended for clients displaying anxiety symptoms or those diagnosed with Social Anxiety Disorder and, as a result, are hindered by their symptoms from interacting with others. By engaging with several bodies of text, exploring Drama Therapy within virtual reality, particularly the use of avatars as roles, provided insight into building the client’s role repertoire. By looking at the different applications of VR across various fields such as the medical, psychotherapeutic and the rehabilitation field, an account of how VR has helped improve their practice was scrutinised under the lens of how it may be applicable within the Drama Therapeutic space using role theory and method. The paper also looked at the various physiological considerations that go into conducting a VR session. A 9-step process of VR was highlighted for the therapist to consider when using VR. The 8- step Role Method technique was used to highlight how a hypothetical nine-step Virtual Reality Drama Therapy (VRDT) session could occur. The application of VR from a South African context was scrutinised, taking into account aspects such as the socio-economic, historical and geographical factors that influence VR adoption in various practices.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Arts to the Faculty of Humanities, Wits School of Arts, University of the Witwatersrand, Johannesburg, 2023